2015
DOI: 10.1177/2040622315579621
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the use of anti-tumor necrosis factor in the management of patients with Crohn’s disease

Abstract: Abstract:Since the approval of the first anti-tumor necrosis factor (anti-TNF) therapy in late 1998, the treatment for Crohn's disease (CD) has been revolutionized. Anti-TNF therapy has been consistently shown in numerous clinical trials to be effective for patients with more aggressive perianal, internal penetrating, and fistulizing CD. However, the loss of clinical remission is frequent and only one-third of patients remain in clinical remission at 1 year. The pharmacokinetics of anti-TNF is highly variable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…The results of our study indicated that half-ED could be effective in improving the long-term prognosis of CD patients treated with anti-TNF-α antibodies, by extending the cumulative retention efficacy of the treatments. Indeed, several retrospective studies from Japanese institutions have reported that the patients, who were treated with IFX and a concomitant elemental diet, exhibited better long-term outcomes than those who were treated with IFX alone [29-33]. The present study strongly supports this previous evidence of the increase in IFX efficacy.…”
Section: Discussionsupporting
confidence: 88%
“…The results of our study indicated that half-ED could be effective in improving the long-term prognosis of CD patients treated with anti-TNF-α antibodies, by extending the cumulative retention efficacy of the treatments. Indeed, several retrospective studies from Japanese institutions have reported that the patients, who were treated with IFX and a concomitant elemental diet, exhibited better long-term outcomes than those who were treated with IFX alone [29-33]. The present study strongly supports this previous evidence of the increase in IFX efficacy.…”
Section: Discussionsupporting
confidence: 88%
“…The majority of clinically approved antibody drugs are antagonists that block specific receptors, such as the case for HER-2/EGF receptors ( 39 , 40 ), or sequester specific proteins, as in the case of anti-TNF or anti-VEGF antibodies ( 41 , 42 ). Conversely, among the vast chemical diversity represented by the human antibody repertoire, it is possible to identify antibodies that activate cell-surface receptors or ion channels.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be acknowledged that our study sample might have included patients who did not receive optimal anti-TNF dosing [ 35 , 36 ]. As previous studies have shown, in fact, only an anti-TNF concentration >3 μg/mL is associated with clinical response and lower disease activity [ 37 ]. Furthermore, multiple factors might affect the pharmacokinetics of anti-TNF levels, including albumin, weight, gender, inflammation, administration route, and immunogenicity [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…As previous studies have shown, in fact, only an anti-TNF concentration >3 μg/mL is associated with clinical response and lower disease activity [ 37 ]. Furthermore, multiple factors might affect the pharmacokinetics of anti-TNF levels, including albumin, weight, gender, inflammation, administration route, and immunogenicity [ 37 ]. Notwithstanding the multiplicity of factors that might influence response to biologic therapy, no single marker has been identified so far as a reliable predictor of response or suboptimal therapy in UC and CD [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%